Case management and psychosocial care services for child and adolescent survivors of rape and sexual abuse - Khadiguia Ontok-Balah (INSPIRA: Indonesian Journal of Psychological Research, 2022)
A child's right to life is violated by sexual abuse, which also represents an abuse of power. The case management and psychological care services provided to the child and adolescent survivors of rape and sexual abuse were evaluated in this study. Three (3) Registered Social Workers and five (5) residents from the Home for Women and Children (HWC) in Amas, Kidapawan City, Philippines, took part in the study. Before the incidents, the residents were all high school students aged 14 to 19 years old. Based on the findings, the caseworkers were unable to provide adequate psychological support, and the staff and the caseworkers were also unable to adequately explain to the residents that they could always return for additional help. The clients were uncomfortable telling their stories, felt blamed by the staff and caregivers for the abuse, were bored in the center, and missed their families, and many were still unsatisfied with the care services offered by the HWC because the perpetrator had not been jailed yet, thus, their home is not yet safe for them. The head of the HWC recommends that the client's integration plan be developed, preferably with a six-month aftercare program or monitoring. Also, there must be suitable strategies to avoid and respond to sexual violence. Clients should receive more outstanding psychosocial care, and employees and caseworkers should receive other pieces of training, seminars, and workshops to improve the services provided in the HWC